Barriers and facilitators to HIV testing among young men who have sex with men and transgender women in Kingston, Jamaica: a qualitative study - Logie, Carmen H. (J Int AIDS Soc, 2017)
Introduction: Young men who have sex with men (MSM) in Jamaica have the highest HIV prevalence in the Caribbean. There is little information about HIV among transgender women in Jamaica, who are also overrepresented in the Caribbean epidemic. HIV-related stigma is a barrier to HIV testing among Jamaica’s general population, yet little is known of MSM and transgender women’s HIV testing experiences in Jamaica. We explored perceived barriers and facilitators to HIV testing among young MSM and transgender women in Kingston, Jamaica. Methods: We implemented a community-based research project in collaboration with HIV and lesbian, gay, bisexual and transgender (LGBT) agencies in Kingston. We held two focus groups, one with young (aged 18–30 years) transgender women (n = 8) and one with young MSM (n = 10). We conducted 53 in-depth individual semi-structured interviews focused on HIV testing experiences with young MSM (n = 20), transgender women (n = 20), and community-based key informants (n = 13). We conducted thematic analysis to identify, analyze, and report themes. Results: Participant narratives revealed social-ecological barriers and facilitators to HIV testing. Barriers included healthcare provider mistreatment, confidentiality breaches, and HIV-related stigma: these spanned interpersonal, community and structural levels. Healthcare provider discrimination and judgment in HIV testing provision presented barriers to accessing HIV services (e.g. treatment), and resulted in participants hiding their sexual orientation and/or gender identity. Confidentiality concerns included: clinic physical arrangements that segregated HIV testing from other health services, fear that healthcare providers would publicly disclose their status, and concerns at LGBT-friendly clinics that peers would discover they were getting tested. HIV-related stigma contributed to fear of testing HIV-positive; this intersected with the stigma of HIV as a “gay” disease. Participants also anticipated healthcare provider mistreatment if they tested HIV positive. Participants identified individual (belief in benefits of knowing one’s HIV status), social (social support) and structural (accessible testing) factors that can increase HIV testing uptake. Conclusions: Findings suggest the need for policy and practice changes to enhance confidentiality and reduce discrimination in Jamaica. Interventions to challenge HIV-related and LGBT stigma in community and healthcare settings can enhance access to the HIV prevention cascade among MSM and transgender youth in Jamaica.